1976
DOI: 10.1038/bjc.1976.88
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Kaposi's sarcoma: Clinical features and therapy

Abstract: Twelve cases of childhood Kaposi's sarcoma seen at the Uganda Cancer Institute over the last 7 years are reported. The disease presents mainly as generalized lymphadenopathy, with sparsely and anomalously distributed cutaneous nodules, and has a higher proportion of females with the disease than in the adult form. The histology is usually of mixed cell type. If not treated, childhood Kaposi's sarcoma runs a fulminating course, but disease control with chemotherapy is associated with prolonged survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…7 Durable responses were seen in all varieties of KS, including childhood lymphadenopathic forms. 28 Similar combinations that substitute adriamycin for actinomycin-D (ABV) in HIVassociated Kaposi's sarcoma have produced high response rates and are regarded by some investigators as the first-line treatment for patients with life-threatening or visceral disease. 25,29 However, several recent studies comparing ABV combination with liposomal doxorubicin or daunorubicin revealed that the liposomal doxorubicin/ daunorubicin was significantly more efficacious in providing objective responses and therefore is now considered by some as first-line therapy for advanced Kaposi's sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…7 Durable responses were seen in all varieties of KS, including childhood lymphadenopathic forms. 28 Similar combinations that substitute adriamycin for actinomycin-D (ABV) in HIVassociated Kaposi's sarcoma have produced high response rates and are regarded by some investigators as the first-line treatment for patients with life-threatening or visceral disease. 25,29 However, several recent studies comparing ABV combination with liposomal doxorubicin or daunorubicin revealed that the liposomal doxorubicin/ daunorubicin was significantly more efficacious in providing objective responses and therefore is now considered by some as first-line therapy for advanced Kaposi's sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…in Central and East Africa) 20 , such as in Uganda 21 . A recent study found HHV-8 infection in early childhood in Uganda unassociated with antibodies to hepatitis A or C virus or with the quality of water supply, which points to a horizontal mode of transmission different to that of developed countries 22 .…”
Section: Epidemiology Of Hhv-8 -Aspects Of Transmissionmentioning
confidence: 99%
“…Epidemic KS in children commonly involves the lymphatic system and results in a more aggressive clinical course compared with the cutaneous and mucosal presentation commonly seen in adults [18,19,26,28,39,65,66]. Children who acquire HIV via perinatal or breastfeeding transmission are at risk for subsequent HHV-8 infection, and the sequence of viral acquisition may play a role in disease progression.…”
Section: Epidemic Ksmentioning
confidence: 99%